Alternative splicing of human metabotropic glutamate receptor 3. - Sartorius, L; Nagappan, G; Lipska, B; Lu, B; Sei, Y; Ren-Patterson, R; Li, Z; Weinberger, DR; Harrison, P (2006)
The metabotropic glutamate receptor 3 (GRM3, mGluR3) is important in regulating synaptic glutamate. Here, we report the existence of three splice variants of GRM3 in human brain arising from exon skipping events. The transcripts are expressed in prefrontal cortex, hippocampus and cerebellum, and in B lymphoblasts. We found no evidence for alternative splicing of GRM2. The most abundant GRM3 variant lacks exon 4 (GRM3Delta4). In silico translation analysis of GRM3Delta4 predicts a truncated protein with a conserved extracellular ligand binding domain, absence of a seven-transmembrane domain, and a unique 96-amino acid C-terminus. When expressed in rat hippocampal neurons, GRM3Delta4 is translated into a 60 kDa protein. Immunostaining and cell fractionation data indicate that the truncated protein is primarily membrane-associated. An antibody developed against the GRM3Delta4 C-terminus detects a protein of approximately 60 kDa in human brain lysates and in B lymphoblasts, suggesting translation of GRM3Delta4 in vivo. The existence of the GRM3Delta4 isoform is relevant in the light of the reported association of non-coding single nucleotide polymorphisms (SNPs) in GRM3 with schizophrenia, and with the potential of GRM3 as a therapeutic target for several neuropsychiatric disorders.